Pelatihan Pembuatan Hand Sanitizer Untuk Mencegah Penyebaran Pandemi Covid-19 Di Dusun Jatisari Desa Krenceng Kediri - Luthfiani Putri; Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
The Covid-19 pandemic has attacked various countries in the world, this problem is not only a problem for the State of Indonesia, but has become a global problem. Various regions in Indonesia have been affected by the Covid-19 pandemic. One of them is in Jatisari Hamlet, Krenceng Village, Kec. Kepung, Kab. Kediri. With the Covid-19 pandemic, people in Jatisari Hamlet, Krenceng Village, are urged to maintain health and implement healthy lifestyle behaviours to prevent the spread of Covid-19. One of them is diligently washing hands with soap or hand sanitiser. Therefore, we as students have a role in community service which is manifested in training activities for making natural hand sanitisers derived from plants in the surrounding environment such as aloe vera and lime in Jatisari Hamlet, Krenceng Village, Kec. Kepung, Kab. Kediri. The purpose of this hand sanitiser manufacturing training is to direct the community, especially the youth of the Hidayatul Muttaqin mosque to take advantage of all the potential and existing materials to be processed into useful preparations. -19. This training was attended by 5 people consisting of teenagers from the Hidayatul Muttaqin mosque in Jatisari Hamlet, Krenceng Village, Kec. Kepung, Kab. Kediri. The training provided was in the form of making hand sanitisers. The result of this training was that the youth of the Hidayatul Muttaqin mosque was very enthusiastic and interested in participating in the training on making natural hand sanitisers that we held.